Vitamin D Pathway Genes, Diet, and Risk of Renal Cell Carcinoma. (31st August 2009) - Karami, S.; Brennan, P.; Navratilova, M.; Mates, D.; Zaridze, D.; Janout, V.; Kollarova, H.; Bencko, V.; Matveev, V.; Szesznia-Dabrowska, N.; Holcatova, I.; Yeager, M.; et al.
Abstract : Mediated by binding to the high-affinity vitamin D receptor (VDR), vitamin D forms a heterodimer complex with the retinoid-X-receptor (RXR). Variation in both genes has been shown to modify renal cell carcinoma (RCC) risk. Therefore, we investigated whether VDR and RXRA polymorphisms modify associations between RCC risk and frequency of dietary intake of vitamin D and calcium rich foods, and occupational ultraviolet exposure among 777 RCC case and 1035 controls from Central and Eastern Europe. A positive association was observed in this population between increasing dietary intake frequency of yogurt, while an inverse association was observed with egg intake frequency. RXRA polymorphisms, located3 ′ of the coding sequence, modified associations between specific vitamin D rich foods and RCC risk, while RXRA polymorphisms, located in introns 1 and 4, modified associations with specific calcium rich foods. Results suggest that variants in the RXRA gene modified the associations observed between RCC risk and calcium and vitamin D intake.